2019
DOI: 10.1262/jrd.2019-046
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine prevents bovine oocyte aging and promotes subsequent embryonic development

Abstract: L-carnitine (LC) is well known for its antioxidant activity. In this study, we explored the potential mechanistic effects of LC supplementation on aged bovine oocytes in vitro. We showed that in-vitro maturation could enhance the subsequent developmental capacity of aging oocytes, when supplemented with LC. After in vitro fertilization, the blastocyst formation rate in the aged oocytes post-LC treatment significantly increased compared to that in untreated aged oocytes (29.23 ± 2.20% vs. 20.90 ± 3.05%). Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
3
20
1
2
Order By: Relevance
“…GSH as an endogenous antioxidant not only maintain the intracellular redox balance, but also is an indicator of cytoplasmic maturation to reflect the oocyte fertilization and subsequent development 41 . There was no reduction of GSH content for aged oocytes in this study, similar to previous reports 42 , 43 ; however, several studies have showed the aged oocytes with lower level of GSH 44 , 45 . Moreover, the aged oocytes treated with Ax exhibited an increase in intracellular GSH content, which is similar to the result of antioxidant hesperetin treatment 42 .…”
Section: Discussionsupporting
confidence: 91%
“…GSH as an endogenous antioxidant not only maintain the intracellular redox balance, but also is an indicator of cytoplasmic maturation to reflect the oocyte fertilization and subsequent development 41 . There was no reduction of GSH content for aged oocytes in this study, similar to previous reports 42 , 43 ; however, several studies have showed the aged oocytes with lower level of GSH 44 , 45 . Moreover, the aged oocytes treated with Ax exhibited an increase in intracellular GSH content, which is similar to the result of antioxidant hesperetin treatment 42 .…”
Section: Discussionsupporting
confidence: 91%
“…The maturation rate reported in the 0.6 mg/mL LC supplemented group was also higher than those demonstrated previously when dog oocytes cultured in vitro for 72 h (0.0% to 6.82% [ 1 ], 25.5% [ 4 ], 2.48% to 13.23% [ 43 ], 5.56% to 21.82% [ 44 ], and 3.8% [ 45 ]). Our findings suggest that LC could positively impact oocyte maturation during a prolonged culture period [ 25 , 46 ]. Regarding the effect of LC on fertilization status following IVF, our results show that treatment of oocytes with 0.6 mg/mL LC during IVM improved fertilization rates compared with the control group and other LC concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The morula percentage reported in [ 9 ] is lower than that reported here in a 0.6 mg/mL LC supplemented group (4.5%). It is known that culturing oocytes for a long period increases ROS accumulation and reduces the antioxidant defense mechanism within the oocytes, creating oxidative stress that harmfully impacts oocyte developmental potential [ 25 , 46 ]. This notion could explain the low rates of embryo development reported in the oocytes matured for 72 h in the study of Otoi et al [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleavage stage and the 4-cell stage are key stages in porcine embryonic development and zygotic genome activation [ 24 ]. Appropriate additives can be beneficial for overcoming blocks in embryonic development and for improving embryonic developmental potential [ 11 , 25 , 26 ]. Therefore, we also investigated the effects of CA on 4-cell-stage embryonic development.…”
Section: Discussionmentioning
confidence: 99%